An immersive virtual reality exergame as a patient education approach in fibromyalgia: Pilot study - Cassandra Lucia Bardelli; Luca Chittaro; Simone Longhino; Luca Quartuccio (Digital Health)
Background Immersive Virtual Reality (VR) has been applied in pain management for various conditions, but its use in fibromyalgia (FM) remains underexplored. While physical activity plays a role in treating FM, patients’ low tolerance often limits its effectiveness. After reviewing the literature on VR and games for FM, we designed a novel VR exergame to assist FM patients in performing physical activity, and evaluate its feasibility. Materials and Methods This pilot study involved three female subjects with FM and four healthy female volunteers. The main outcomes included qualitative assessments of exertion, pain levels, psychological states experienced during the VR session, but also device comfort. Results Improvements in perceived exertion and pain intensity were observed during the VR exergame session in comparison to pre-exergame levels, along with a reduction in depression, stress and anxiety levels while using the VR immersive system. Most participants experienced also increase of relaxation and positive emotions during the exergame. Only one participant was not able to complete all levels of the exergame due to musculoskeletal pain exacerbation; nevertheless, this patient reported an improvement in motivation and enjoyment during the gameplay. Many participants expressed a greater motivation to perform the exercises in the VR environment compared to traditional training methods. Conclusion The proposed VR exergame is a feasible system that might reduce depression, stress and anxiety, while boosting motivation and relaxation in both healthy and FM subjects. A calibration protocol is required to tailor the system to each user's pain levels and physical abilities.